Otis Worldwide CEO Judy Marks (Thirty Minute Mentors). - Mendler | Thirty Minute Mentors, Adam (linkedin.com, 2022)
Learn about the key characteristics of effective and successful leadership in this audio-only course with Judy Marks, the CEO of the Otis Elevator Company.